Acceptability and satisfaction towards self‐collection for chlamydia and gonorrhoea testing among transgender women in Tangerine Clinic, Thailand: shifting towards the new normal. Issue 9 (8th September 2021) - Hiransuthikul, Akarin; Janamnuaysook, Rena; Himma, Linrada; Taya, Chiraporn; Amatsombat, Tidarat; Chumnanwet, Phongdanai; Samitpol, Kritima; Chancham, Artsanee; Kongkapan, Jiratchaya; Rueannak, Jeeranuch; Getwongsa, Pintusorn; Srimanus, Peevara; et al.
Abstract: Introduction: Provider‐collected swabs are an unappealing procedure for many transgender women and may have led to suboptimal rates of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) testing. Self‐collection for CT/NG testing is recommended for men who have sex with men. However, the information on acceptability and clinical performance to support a recommendation for transgender women is lacking. We aimed to determine the acceptability and satisfaction towards self‐collection for CT/NG testing among Thai transgender women. Methods: Thai transgender women who attended Tangerine Clinic (a transgender‐led, integrated, gender‐affirming care and sexual health services clinic in Bangkok, Thailand) between May and July 2020 and had condomless sexual intercourse within the past six months were offered to collect urine and perform self‐swabs of pharyngeal, rectal, and if applicable, neovaginal compartments for pooled nucleic acid amplification testing for CT/NG infections. Participants received a diagram, video and oral instructions about how to perform self‐collection procedure. Those who accepted self‐collection were also offered to receive provider collection to evaluate the performance between the two methods. Self‐administered questionnaires were used to assess satisfaction. Results: Among 216 transgender women enrolled, 142 (65.7%) accepted self‐collection. All who accepted had pharyngeal, rectal and urine samples collected. Of 31 transgender women who had undergone genital surgery, 28 (90.3%) accepted neovaginal self‐swab. The acceptance rate increased from 46.2% in May to 84.5% in July 2020. One participant had an invalid result. All transgender women who accepted self‐collection could perform it without assistance, and 82.8% were highly satisfied with the method. None reported dissatisfaction. Due to the COVID‐19 pandemic, provider collection services were discontinued early, and only eight transgender women were able to perform both methods for performance evaluation. The performance agreement was 100%. Conclusions: Thai transgender women had high acceptability and satisfaction towards self‐collection for CT/NG testing. The performance was promising compared to provider collection. Our results support the implementation of self‐collection to the sexually transmitted infection services, particularly during the COVID‐19 pandemic where physical distancing is the new normal. A larger study is warranted to determine the performance of self‐collection for CT/NG testing in each anatomical compartment and confirm the performance between self‐collection and provider collection.